Pengenalan E-Modul Berbasis PBL Terintegrasi Kearifan Lokal untuk Meningkatkan Literasi dan Keterampilan Proses Siswa di SMPN 15 Mataram - Baiq Nabila Saufika Zainuri; Gunawan Gunawan; Kosim Kosim (Indonesian Publication Center, 2025)
The purpose of this activity is to introduce and facilitate the use of an e-module based on Problem-Based Learning (PBL) integrated with local wisdom in the learning process. This activity utilizes a Participatory Action approach consisting of three stages: introduction, training, mentoring, and evaluation. In the introduction phase, the e-module concept was presented to teachers and students through interactive presentations and discussions. The training phase was conducted in the form of a workshop involving students, focusing on the use of the e-module and the implementation of PBL strategies. Subsequently, the mentoring and evaluation phase involved classroom observations and reflective discussions with teachers. The results of the activity show that this e-module has a positive impact on increasing student engagement, strengthening science process skills, improving science literacy, and connecting science learning with local cultural contexts. It is hoped that this approach can continue to be developed and implemented more widely to support more contextual and meaningful learning.